Properties of Mixed System of N‐Coco Propylene Bis‐guanidine Acetate (CPGA) and Nonionic Surfactants. Issue 32 (23rd August 2021) - Li, Jun; Li, Yunling; Wang, Zhifei; Zhang, Lu; Jiang, Yajie; Zhang, Wei; Wu, Junli
Abstract: To study the effect of nonionic surfactant on the properties of cationic surfactant N‐coco propylene bis‐guanidine acetate (CPGA), different ratios of CPGA and fatty alcohol polyoxyethylene ether (AEO9 ) or alkyl polyglycoside (APG1214) were mixed, respectively. The surface activity, interaction parameters, and the application performances of wetting, emulsification and foam of the mixed system were investigated systematically. After the addition of AEO9 or APG1214, the critical micelle concentration (CMC) of mixed system changes distinctly. The results of interaction parameters indicate that the synergistic effects exist between CPGA and AEO9 or APG1214, and the micellizations of the mixtures are spontaneous. The change trend of the equilibrium contact angle is similar to that of the surface tension at CMC ( γCMC ) for the corresponding mixed system. The improvement of wettability of CPGA by AEO9 is significantly stronger than that by APG1214. The emulsifying capacity of CPGA to liquid paraffin or soybean oil is almost enhanced by AEO9 or APG1214. AEO9 has clear defoaming effect on CPGA, and only a small amount of APG1214 can increase the foam stability of CPGA. Abstract : Different ratios of AEO9 or APG1214 were added to CPGA, they both can reduce the CMC value and improve most of the application performances of the single CPGA. Furthermore, results of interaction parameters imply that the synergistic effect exist in the mixed system.